The Impact of Mental Accounting and Self-Control on the Daily Expenses of Students - Nahima Ahista; M. Ali Fikri (Formosa Journal of Multidisciplinary Research, 2024)
Students frequently have challenges in effectively managing their funds, particularly when it comes to daily expenses, as they play a significant role in their academic lives. It is crucial to comprehend the factors that impact students' decision-making process when it comes to controlling their everyday spending. Mental accounting and self-control are crucial psychological concepts that play a significant role in financial decision-making. This research data is classified as primary data. The research collected primary data from students at Mataram University, which was subsequently processed using software applications to transform it into quantitative data. The population for this research consists of all students enrolled at Mataram University across different study programs and academic levels. In this study, the researchers employed the Probability Sampling technique known as Simple Random Sampling for sample selection. The findings from the experimentation indicate that both mental accounting and self-control exert a favorable impact on the everyday expenditures of students. Students who possess a heightened degree of Mental Accounting have a heightened awareness of their expenditure patterns. They scrutinize their expenditures with greater attention and allocate their funds into specific categories, hence facilitating better control over their expenses. In a similar vein, pupils with a strong sense of self-control tend to have a lower daily expenditure. Additionally, they exhibit greater self-control when it comes to managing their everyday finances.